Predicting compound coastal inundation in 2100 by considering the joint probabilities of landfalling tropical cyclones and sea-level rise - Y Peter Sheng; Kun Yang; Vladimir A Paramygin (Environmental Research Letters, 2022)
In the twenty-first century, the effects of sea-level rise (SLR) and more intense tropical cyclones (TCs) are increasing compound coastal inundation worldwide. To facilitate the adaptation efforts being made by coastal communities, here, we use a coastal surge-wave model together with a novel statistical approach to incorporate the six joint probability density functions (PDFs) of five landfall TC parameters and SLR values, instead of the traditional five-parameter approach, which considers the five PDFs of TCs with prescribed SLR values as boundary conditions. The five-parameter approach determines the 1% annual chance of coastal inundation by conducting numerous sets of surge-wave simulations, each for a different SLR scenario, for the future TC ensemble. The six-parameter approach, however, uses a future TC and SLR ensemble to conduct only one set of surge-wave simulations without the subjective selection of an SLR scenario, and is much less uncertain and much more efficient. In this paper, we focus on the 1% risk of inundation in a large coastal flood plain in southwest Florida by incorporating intensifying TCs and accelerating SLR under a representative concentration pathway 8.5 climate scenario in 2100. The 1% risk of inundation determined by the six-parameter approach is comparable to that obtained from the traditional approach forced with the expected SLR value in 2100. The total inundation volume, total inundation area, average inundation height, and maximum inundation height are expected to dramatically increase by (5.7, 2.4, 2.6, and 2.5) times, respectively, compared to their 1982–2009 values. The coastal inundations caused by TCs and SLR are found to interact nonlinearly over the coastal flood plain. Near the coast, TCs account for 70%–80% of the total 1% inundation risk for 1 m of SLR and 30%–70% for 2 m of SLR. Therefore, future inundation analyses must consider TCs and their nonlinear interaction with SLR-induced inundation. These findings will inform local communities and help them to develop coastal adaptation plans.